Marpege-Pege: A Tradition in Batak Angkola Padangsidimpuan - Hasibuan, Alika Sandra; Setia, Eddy (TALENTA Publisher, 2023)
The purpose of this research is to describe the patterns and forms of speech of performers or participants in the performance of the marpege-pege tradition in the Batak Angkola Padangsidimpuan. The method used in this research is the ethnographic method which is carried out by collecting data through in-depth interviews with event leaders, both performers and participants in the tradition itself. To understand the performance displayed, the data collected was analyzed using domain analysis and component analysis methods to obtain the role of participation or performers that was performed. From the findings, it was found that the performance of the performers in the Angkola Padangsidimpuan marpege-pege Batak shows the performers and participants as part of the performance. And for the performer component itself, it can be seen with their respective roles in the utterances or utterances conveyed by performers or participants. Then there are 2 functions of utterances or utterances in this tradition, namely declarative and imperative.